2017
DOI: 10.1051/kmae/2017033
|View full text |Cite
|
Sign up to set email alerts
|

Alien freshwater polychaetesHypania invalida(Grube 1860) andLaonome calidaCapa 2007 in the Upper Odra River (Baltic Sea catchment area)

Abstract: -Two polychaete species, Hypania invalida and Laonome calida, were found in the Upper Odra River in 2016. Both species were recorded close to a natural river bank down to 1 m depths. They inhabited sandy-gravelly and sandy-muddy sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
1
4
1
Order By: Relevance
“…Our research has revealed the upstream dispersion of H. invalida along the Oder River and to the initial section of the Gliwice Canal. Previous research identified its presence at 108 km in the Oder (Pabis et al, 2017). Two years later, we detected this polychaete at 95.3 km, confirming its potential to move upstream.…”
Section: Distribution Of H Invalida and Environmental Conditionssupporting
confidence: 80%
See 2 more Smart Citations
“…Our research has revealed the upstream dispersion of H. invalida along the Oder River and to the initial section of the Gliwice Canal. Previous research identified its presence at 108 km in the Oder (Pabis et al, 2017). Two years later, we detected this polychaete at 95.3 km, confirming its potential to move upstream.…”
Section: Distribution Of H Invalida and Environmental Conditionssupporting
confidence: 80%
“…To date in Poland, H. invalida has only been recorded in the Oder River. It has been found in the estuary area (Wozniczka et al, 2011) and the upper reaches of the river (Pabis et al, 2017). Taking the above findings into account, the aims of our research were: (1) to map the distribution of H. invalida in the upper Oder and associated aquatic environments, (2) to assess the contribution of H. invalida to the benthic fauna, (3) to identify environmental factors linked to the occurrence of H. invalida, (4) to provide genetic markers that can be used to identify H. invalida and monitor its dispersal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its estuary is considered to be one of the most exposed environments for the introduction of alien species in the Baltic Sea catchment. As the main harbour, it plays an important role in both marine and inland shipping and is regarded as a significant gateway for the dispersal of nonindigenous species (Gruszka, 1999;Bij de Vaate et al, 2002;Galil et al, 2008;Gruszka and Woźniczka, 2008;Leuven et al, 2009;Gruszka et al, 2013;Pabis et al, 2017). The number of alien macroinvertebrate species in the Oder River is still growing.…”
mentioning
confidence: 99%
“…It is worth adding that the increasing salinity of aquatic environments contributes to the spread of non-native annelid species. For example, Halabowski et al (2019) observed the presence of the Asian oligochaete species Monopylephorus limosus (Hatai, 1898) in the Bolina River (the Upper Silesian Coal Basin, Poland), which is highly contaminated with saline water associated with underground mining, and Pabis et al (2017) reported the occurrence of the alien polychaete species Laonome calida Capa, 2007 (now considered to be a new species L. xeprovala Bick & Bastrop (Bick et al, 2018)), and Hypania invalida (Grube, 1860) in the brackish waters of the Odra River.…”
Section: Discussionmentioning
confidence: 99%